Abnormal cervical smears in the unchanged uterine cervix: difficulties in the screening, diagnosis, and treatment of cervical intraepithelial neoplasias and microinvasive cancer - L. I. Korolenkova (ABV-press, 2014)
The author analyzes an algorithm for identifying and treating w omen with cervical intraepithelial neoplasias (CIN) and microinv asive cancer of the cervix uteri in cases of the hidden area of transformation and in the absence of visible cervical changes. There are excep- tional difficulties of making the diagnosis of epithelial damages due to the incomplete reproducibility of cytological abnormal ities and the low informative value of a histological study of scrapes from the cervical canal. To avoid hypodiagnosis, it is justifiable to prefer human papillomavirus testing (Hybrid Capture 2 (HC2)) to repeat smears for the choice of a management tactic. Conization is recommend ed as a diagnostic and/or therapeutic procedure when the viral load is high in over 35-year-old patients with abnormal smears anda hidden transformation area.